2017
DOI: 10.1002/ece3.3536
|View full text |Cite
|
Sign up to set email alerts
|

Long-term antagonistic effect of increased precipitation and nitrogen addition on soil respiration in a semiarid steppe

Abstract: Changes in water and nitrogen (N) availability due to climate change and atmospheric N deposition could have significant effects on soil respiration, a major pathway of carbon (C) loss from terrestrial ecosystems. A manipulative experiment simulating increased precipitation and atmospheric N deposition has been conducted for 9 years (2005–2013) in a semiarid grassland in Mongolian Plateau, China. Increased precipitation and N addition interactively affect soil respiration through the 9 years. The interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 75 publications
2
4
0
Order By: Relevance
“…Increased soil respiration under the 8‐year N addition in this old‐field system agrees with the results of numerous previous studies in grasslands (Feng et al, 2017; Jia et al, 2012; Zhang et al, 2014; Zhou et al, 2014), but differs with those in forests (Janssens et al, 2010), semiarid grasslands (Du et al, 2018; Han et al, 2017; Song et al, 2021), and alpine grasslands (Wang et al, 2019) that reported negative N effects on soil respiration. A previous meta‐analysis has found that differences in soil respiration responses to N addition may largely result from diverse responses of root respiration among biomes (Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increased soil respiration under the 8‐year N addition in this old‐field system agrees with the results of numerous previous studies in grasslands (Feng et al, 2017; Jia et al, 2012; Zhang et al, 2014; Zhou et al, 2014), but differs with those in forests (Janssens et al, 2010), semiarid grasslands (Du et al, 2018; Han et al, 2017; Song et al, 2021), and alpine grasslands (Wang et al, 2019) that reported negative N effects on soil respiration. A previous meta‐analysis has found that differences in soil respiration responses to N addition may largely result from diverse responses of root respiration among biomes (Zhou et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Numerous studies have demonstrated that interannual variability of precipitation amount or soil water availability plays a critical role in regulating temporal variations of soil respiration through controlling root and microbial activities and plant growth (Han et al, 2017; Wan et al, 2007; Zhou et al, 2007). In addition, there is also increasing evidence that plant community is a key driver of soil respiration response in long‐term studies (Du et al, 2018; Xu et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of N and P deposition, there were strong monthly variabilities in RS, RA, and RH, which were similar to previous studies [24,53]. Some studies found that temporal variabilities of soil carbon fluxes were driven by precipitation or SM through regulating root and microbial activities [59,60]. However, SM was not the regulating factor controlling RS, RA, and RH, because there were no significant correlations between RS, RA, and RH and SM in the current study (Figure S1).…”
Section: Monthly Dynamics Of Carbon Fluxes and Their Correlations Wit...supporting
confidence: 87%
“…However, there are also mounting evidence suggest a weak prediction of water availability to the N‐induced changes in ecosystem carbon fluxes (Hooper & Johnson, 1999; Lebauer & Treseder, 2008; Niu et al., 2009; Peng et al., 2017). Although GPP is more sensitive to water availability than R e in grassland (Xia et al., 2009), water may also alleviate (Zhang et al., 2017) or enhance (Han et al., 2017) the negative effects of N enrichment on respiration by mediating N‐induced soil acidification. Through decades of researches, we have only acquired knowledge about comparisons of N‐induced effects in dry or wet conditions, there remain considerable knowledge gap about how the N‐induced changes of carbon fluxes, inter‐ or intra‐annually, will vary with water conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It reported that N‐induced stimulation of biomass accumulation (Lü et al., 2011) may exert positive and N‐induced soil acidification (Bowman et al., 2008; Fierer & Jackson, 2006; Ye et al., 2018) may exert negative effects on respiration. Therefore, respiration may increase (Peng et al., 2017; Zhang et al., 2017), remain unchanged (Liu et al., 2018), or decrease (Han et al., 2017) due to N enrichment. Different responsive rates of GPP and R e may lead to positive (Niu et al., 2008; Tian et al., 2016; Xia et al., 2009), negative (Bubier et al., 2007; Saarnio et al., 2003), and neutral (Harpole et al., 2007; Huang et al., 2015; López‐Blanco et al., 2018) responses of NEE to N additions.…”
Section: Introductionmentioning
confidence: 99%